Analysis of Factors Related to Compliance With The Use of Personal Protective Equipment (PPE) on Construction Workers at PT. Jaya Kusuma Sarana (PT. JKS) - Desy Ayu Arifin; Ratih Pramitasari; Kristin Ishak Kurnia Dwi; Anyelir Khailla Eurissetaqtha (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
1)Background: Human resources are one part of the company. Therefore a sound management system is needed. A work accident can be from one of the human factors, namely, not obeying PPE. Therefore, current occupational health and safety issues are not only an obligation that must be paid attention to by workers but also must be fulfilled by the work system because this is a demand that every worker must meet. 2) Objective: This study aims to analyze the factors related to compliance with the use of personal protective equipment (PPE) in construction project workers at PT. JKS 2021. 3) Method: This research was conducted using an analytical observational method with a cross-sectional design of construction workers to construct GBI NDC by PT. JKS. The number of samples in this study was 96 construction workers at PT. JKS. The data is processed using the Spearman rank test. 4) Result: The results showed the behavior of the use of PPE workers at PT. JKS in the construction was good (60 workers) with a percentage of 62.5%. There was a relationship between knowledge and supervision with compliance with the use of PPE on construction project workers of GBI NDC construction by PT. JKS with each value (P-value 0.008) and (P-value 0.020) while there is no relationship between attitude and motivation with compliance with the use of PPE with each value (P-value 0.880) and (P-value 0.628). 5) Conclusion: There was a relationship between knowledge and supervision with the use of PPE on construction workers at PT. JKS.